1996
DOI: 10.1007/bf00033095
|View full text |Cite
|
Sign up to set email alerts
|

Major genes for resistance to beet necrotic yellow vein virus (BNYVV) in Beta vulgaris

Abstract: Inheritance of resistance to beet necrotic yellow vein virus (BNYVV) was studied in segregating F2 and backcross families obtained from crosses between resistant plants of the sugar beet selection Holly-l-4 or the wild beet accession Beta vulgaris subsp . maritima WB42 and susceptible parents . Greenhouse tests were carried out, in which seedlings were grown in a mixture of sand and infested soil . Virus concentrations of BNYVV in the rootlets were estimated by ELISA . To discriminate resistant and susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 16 publications
1
30
1
2
Order By: Relevance
“…maritima Arcang). Characteristics of both accessions were described by Scholten et al (1996). Resistant F 1 families obtained after crossing of Holly-1-4 or WB42 accessions in pairs with plants of one susceptible sugar beet genotype 261 (which is a self-fertile genotype and segregates for nuclear male sterility A:aa) and one annual beet accession from Sugar Beet Seed Institute.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…maritima Arcang). Characteristics of both accessions were described by Scholten et al (1996). Resistant F 1 families obtained after crossing of Holly-1-4 or WB42 accessions in pairs with plants of one susceptible sugar beet genotype 261 (which is a self-fertile genotype and segregates for nuclear male sterility A:aa) and one annual beet accession from Sugar Beet Seed Institute.…”
Section: Methodsmentioning
confidence: 99%
“…Some investigations showed that resistance in WB42 is controlled by another dominant gene (Rz 2 ) (Lewellen 1995, Scholten et al 1997, Francis 1999. But, the exact number of resistance genes remained unclear (Lewellen et al 1987, Whitney 1989, Scholten et al 1996, 1997, ⎯⎯⎯⎯ 1999. However, Amiri et al (2003aAmiri et al ( , 2003b reported that the resistance to rhizomania in WB42 is controlled by one dominant gene.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…These results suggest that the factor for resistance to BNYVV in MR1 and MR2 lines is dominant and simply inherited, consistent with several previous observations that resistance to BNYVV in B. vulgaris subsp. maritima or in the Holly source is controlled by a single dominant gene (Lewellen et al 1987;Scholten et al 1996;Whitney 1989). One homogeneous plant line derived from BGRC54778 that had the YS phenotype was designated B. vulgaris subsp.…”
Section: Beet Necrotic Yellow Vein Virus (Bnyvv Genus Benyvirus)mentioning
confidence: 98%